Development of a novel dual heated cascade supercritical carbon dioxide cycle and performance comparison with existing two configurations for waste heat recovery. (5th May 2021) - Lin, Xinxing; Chen, Chonghui; Yin, Likun; Su, Wen; Zhou, Naijun
Summary: As an efficient method for the waste heat recovery of gas turbine, supercritical carbon dioxide (S‐CO2 ) power cycle has gained much attention, due to the high efficiency and compact structure. Thus, in this work, a novel S‐CO2 power cycle is developed for the waste heat recovery via the modification of dual heated cascade cycle with an intercooler (intercooling cycle). Compared with the dual heated cascade cycle (original cycle) and the intercooling cycle, the novel cycle has independent pressures at different heaters and turbines. To analyze the system performance, thermodynamic models are established and a genetic algorithm (GA) is applied to optimize the decision variables with the maximization of net work. These variables include two turbine inlet temperatures, a middle pressure, a low pressure, and a split ratio. Thereafter, thermodynamic parameters of the considered three cycles are obtained under different waste gas temperatures. For the recovery of 600°C waste gas, the novel cycle has the highest net work 3957.87 kW, while the lowest net work 3735.32 kW is obtained by the original cycle. For the effects of decision variables, a higher high‐temperature turbine inlet temperature means a lower net work, while the increase of low‐temperature turbine inlet temperature results in small increases of cycle performances. On the other hand, under the constraints of the pinch point, with the increase of low and middle pressures, the net work of the novel cycle increases. A higher net work is usually obtained at a lower split ratio. Furthermore, at different waste gas inlet temperatures, the highest cycle efficiency is always derived by the proposed cycle. For the net work, the proposed cycle has the highest value in the temperature range 600°C–750°C.